At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
EXPLANATION
[tex]\int \frac{(\ln x)^{96}}{x}dx[/tex]Applying subtitution: u=ln(x)
By integral substitution definition
[tex]\int f(g(x))\cdot g^{^{\prime}}(x)dx=\text{ }\int f(u)du,\text{ u=g(x)}[/tex]Substitute: u=ln(x)
[tex]\frac{du}{dx}=\frac{1}{x}[/tex][tex]\frac{d}{dx}=(\ln (x))[/tex]Apply the common derivative:
[tex]\frac{d}{dx}(\ln (x))=\frac{1}{x}[/tex][tex]\Rightarrow du=\frac{1}{x}dx[/tex][tex]\Rightarrow dx=xdu[/tex][tex]=\int \frac{u^{96}}{x}\text{xdu}[/tex]Simplify:
[tex]\frac{u^{96}}{x}x[/tex]Multiply fractions:
[tex]a\cdot\frac{b}{c}=\frac{a\cdot b}{c}[/tex][tex]=\frac{u^{96}x}{x}[/tex]Cancel the common factor: x
[tex]=u^{96}[/tex][tex]=\int u^{96}du[/tex]Apply the Power Rule:
[tex]\int x^adx=\frac{x^{(a+1)}}{a+1},\text{ a }\ne\text{ -1}[/tex][tex]=\frac{u^{96+1}}{96+1}[/tex]Substitute back u=ln(x)
[tex]=\frac{\ln ^{96+1}(x)}{96+1}[/tex]Simplify:
[tex]\frac{\ln ^{96+1}(x)}{96+1}[/tex]Add the numbers: 96+1=97
[tex]=\frac{\ln ^{97}(x)}{97}[/tex][tex]=\frac{1}{97}\ln ^{97}(x)[/tex]Add a constant to the solution:
[tex]=\frac{1}{97}\ln ^{97}(x)\text{ + C}[/tex]The answer is D:
[tex]\frac{(\ln x)^{97}}{97}+C[/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.